2014
DOI: 10.1007/s00299-014-1690-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal localization of homogalacturonans in Hyacinthus orientalis L. ovule cells before and after fertilization

Abstract: Key message The composition of homogalacturonans (HGs) in the ovule and the female gametophyte cell walls was shown to be rearranged dynamically during sexual reproduction of H. orientalis. Abstract In angiosperms, homogalacturonans (HGs) play an important role in the interaction between the male gametophyte and the pistil transmitting tract, but little is known about the participation of these molecules at the final stage of the progamic phase and fertilization. The aim of our study was to perform immunocytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 75 publications
4
20
1
Order By: Relevance
“…In contrast to amphimictic plants (e.g. Galanthus , Śnieżko and Chudzik 2003; Olea , Suárez et al 2013; Hyacinthus , Niedojadło et al 2015), we did not observed abundant occurrence of highly methyl-esterified HG labelled by the JIM7 antibody in either the micropyle or the synergids of apomictic Taraxacum . Neither of the two HG domains (recognised by JIM7 and JIM5 antibodies) were recorded in the micropylar part of the embryo sac nor in the cytoplasm of the synergids in apomict C. juncea (Kościńska-Pająk et al 2005; Kościńska-Pająk 2006).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…In contrast to amphimictic plants (e.g. Galanthus , Śnieżko and Chudzik 2003; Olea , Suárez et al 2013; Hyacinthus , Niedojadło et al 2015), we did not observed abundant occurrence of highly methyl-esterified HG labelled by the JIM7 antibody in either the micropyle or the synergids of apomictic Taraxacum . Neither of the two HG domains (recognised by JIM7 and JIM5 antibodies) were recorded in the micropylar part of the embryo sac nor in the cytoplasm of the synergids in apomict C. juncea (Kościńska-Pająk et al 2005; Kościńska-Pająk 2006).…”
Section: Discussioncontrasting
confidence: 73%
“…Wolf et al 2009). It has been well documented that homogalacturonan (HG) plays an important role in pollen-stigma and pollen tube-pistil interactions in flowering plants (see Sage et al 2009; Niedojadło et al 2015 and discussion therein). In amphimictic plants, there are pollination- and fertilisation-induced changes in the occurrence of highly (JIM7) and low (JIM5) methyl-esterified pectins in the pistil transmitting tract, the micropyle of the ovule and also in the apoplast of female gametophyte cells (Lenartowska et al 2001; Śnieżko and Chudzik 2003; Suárez et al 2013; Niedojadło et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial cultivars of Hyacinthus orientalis L. were grown at room temperature. The Hyacinthus pistil is composed of a hollow style and a dry stigma, while the female gametophyte develops according to the Polygonum type and consists of two synergids, the egg cell, the central cell containing two polar nuclei, and three antipodals (Pięciński et al 2008 ; Niedojadło et al 2012a , b , 2015 ). For fluorescence and electron microscopy studies, the ovules were mechanically dissected from unpollinated flowers before and during anthesis and from hand-cross-pollinated flowers 8 h after pollination (at the late progamic phase when the pollen tubes have reached approximately three-quarters of the style length and have not entered the ovary) and 96 h after pollination (fertilized ovules).…”
Section: Methodsmentioning
confidence: 99%
“…Studies performed in several eudicots support an association of a decrease in calcium levels with a loss of receptivity, whereas an abundance of calcium in the synergids is associated with pollen tube penetration (Ge et al, 2007). Moreover, free calcium that can be released from homogalacturonans in the micropylar secretion has been related to pollen tube elongation in Hyacinthus orientalis (Niedojadło et al, 2015) and Haemanthus albiflos (Lenartowska et al, 2011). Recently, AGPs in the secretion of the obturator have also been reported to mediate pollen tube access to the micropyle in Malus 9 domestica, the apple (Losada & Herrero, 2017).…”
Section: Introductionmentioning
confidence: 99%